Horner's Syndrome as a rare complication of tube thoracostomy: Case reports and review of literature - KIYAN, GÜRSU (W B SAUNDERS CO-ELSEVIER INC, 2013)
Horner's Syndrome (HS), caused by the interruption of the oculosympathetic pathway, is a rare yet morbid complication of tube thoracostomy. However, literature regarding HS secondary to tube thoracostomy is limited to case reports, with little comprehensive information available. We report two cases and review all cases from the published literature to assess the outcome of this complication. HS secondary to tube thoracostomy leaves sequelae in 45.8% of patients. Immediate removal or repositioning of the tube does not affect prognosis. Therefore, precautions must be taken to avoid this complication. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Horner's Syndrome; Tube thoracostomy; Complication; SPONTANEOUS PNEUMOTHORAX; SYNDROME SECONDARY; CHEST DRAIN